Anti-trafficking data collection in Europe. A review based on the GRETA’s evaluations with the 2005 Council of Europe Convention against Human Trafficking - Villanueva-Fernández, Alba (Iberoamerican Journal of Development Studies, 2023)
The configuration of human trafficking and the more effective frame to combat it have been determined in the last twenty years. With the Palermo Protocol and the Warsaw Convention, the human rights-based approach is in the center of the proposal. One of its main features requires establishing a data collection system to facilitate and control the reality of human trafficking in the country. In this study, it is intended to comparative analyze the data collection of trafficking victims in Europe. In the analysis, it is concluded that the disparity of what is being counted puts the comparison at risk. At the same time, the human rights-based approach to trafficking is contested.
Keywords: human trafficking; Council of Europe; Convention against Human Trafficking; human rights approach; data collection; comparative politics